Application and reflections on efficient development of deep oil and gas reservoirs in Tarim Basin - HU Wenge, MA Longjie, WANG Yan, BAO Dian, ZHANG Yun (Youqicang pingjia yu kaifa)
The economic development of oil and gas reservoirs in the Tarim Basin is challenged by their complex nature and substantial investment costs. This paper primarily summarizes the intricacies of deep oil and gas reservoirs across four dimensions: accumulation conditions, reservoir space types, internal structures, and changes in hydrocarbon composition. It also explores three core issues that hinder efficient utilization, enhanced recovery, and economic growth of these reservoirs, along with proposed countermeasures. To address these challenges effectively, the paper proposes four research directions: ①A prediction method for reservoir characteristics that integrates the processes of near-source generation, transportation, storage, and cap rock formation. ②A quantitative parameter characterization method for identifying deep fractures and preserving caverns. ③A characterization method for differentiating fracture boundaries and assessing their internal connectivity. ④The establishment of a comprehensive life cycle economic evaluation system for ultra-deep domains, alongside differentiated development strategies. These strategies offer valuable suggestions towards achieving efficient development of deep to ultra-deep carbonate reservoirs and ensuring national energy security.